2006
DOI: 10.1542/peds.2005-2724
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality of Infants With Very Low Birth Weight in Japan: Center Variation

Abstract: The overall survival rate for very low birth weight infants among neonatal centers in Japan was approximately 90%. However, differences in the morbidity and mortality were observed among these centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
181
7
13

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(212 citation statements)
references
References 15 publications
11
181
7
13
Order By: Relevance
“…The higher incidence of severe intraventricular hemorrhage observed in the <34 weeks GA compared with the ≥34 weeks GA group was also an expected observation, given that babies born at an earlier GA are known to be at increased risk for severe intraventricular hemorrhage [24,25]. This finding was also consistent with findings from a larger Japanese observational study conducted by Kusuda and colleagues [26], which showed that in the 2145 very low birthweight infants studied (mean [SD] birthweight, 1024 [302] g; mean [SD] GA, 28.9 [3.4] weeks), the observed incidence of grade 3 or 4 intraventricular hemorrhage was 7%. In prospective, controlled studies of iNO conducted in premature neonatal populations with respiratory failure in the United States, the overall safety profile observed (including reported incidences of intraventricular hemorrhage) has been similar in the iNO treatment arms compared with patient groups who received placebo or no iNO [27][28][29][30][31][32].…”
Section: Discussionsupporting
confidence: 85%
“…The higher incidence of severe intraventricular hemorrhage observed in the <34 weeks GA compared with the ≥34 weeks GA group was also an expected observation, given that babies born at an earlier GA are known to be at increased risk for severe intraventricular hemorrhage [24,25]. This finding was also consistent with findings from a larger Japanese observational study conducted by Kusuda and colleagues [26], which showed that in the 2145 very low birthweight infants studied (mean [SD] birthweight, 1024 [302] g; mean [SD] GA, 28.9 [3.4] weeks), the observed incidence of grade 3 or 4 intraventricular hemorrhage was 7%. In prospective, controlled studies of iNO conducted in premature neonatal populations with respiratory failure in the United States, the overall safety profile observed (including reported incidences of intraventricular hemorrhage) has been similar in the iNO treatment arms compared with patient groups who received placebo or no iNO [27][28][29][30][31][32].…”
Section: Discussionsupporting
confidence: 85%
“…Nuestras cifras también son parecidas a las de un estudio de tendencias de mortalidad y morbilidad en RNMBPN en América del Norte en el período 1990 y 1991, que muestra un cambio respecto a la intervención prenatal con el uso de corticoides con un incremento de uso del 23,8% en 1991 a 71,6% en 1999 (12). Otro estudio en Japón, con 2.145 RNMBPN, describe un 41% de su uso, con un amplio rango de variación en los 37 centros evaluados (13). Por último, y realmente notable es la información del reporte clínico anual del 2005 del informe del Nacional Women´s Hospital en Auckland Nueva Zelanda donde se comunica que el 94% de los RN menores de 32 semanas de gestación recibió corticoides antenatales, y un 88% en el periodo 1995-2003 (14).…”
Section: Tabla IX Comparación De Los Resultados De Los Rnebpn Hospitunclassified
“…5 A large multicenter survey report, including 37 Japanese NICUs of level III intensive cares and 2,145 VLBW infants, revealed that the incidence of sepsis was 8% in 2003. 24 The Neonatal Research Network of Japan also reported that 492 (5.0%) of 9,812 VLBW infants, who were born from 2006-2008, developed LOS (Table 1). 25 A current issue is how to control and prevent LOS in VLBW infants in Japan.…”
Section: Recent Epidemiology Incidencementioning
confidence: 98%